Early switch from run-in with targeted to immunotherapy in advanced BRAFV600-positive melanoma: final results of the randomised phase II ImmunoCobiVem trial - Livingstone, Elisabeth; Gogas, H. J.; Kandolf, L.; Meier, F.; Eigentler, T. K.; Ziemer, M.; Terheyden, P.; Gesierich, A.; Herbst, R. A.; Kähler, K. C.; Ziogas, D. C.; Mijušković, Ž.; et al. (ESMO open, 2025)
Background - Optimal sequencing of immune checkpoint inhibitors (ICIs) and targeted therapies (TTs) in BRAFV600-positive advanced melanoma should achieve rapid tumour control and durable progression-free survival (PFS), translating into prolonged overall survival (OS). - Patients and methods - The 1 : 1 randomised phase II ImmunoCobiVem trial compared—after a 3-month run-in phase with vemurafenib (VEM, 960 mg twice daily) and cobimetinib (COB, 60 mg daily days 21-28, q4w)—continuous VEM + COB until disease progression (PD1) and second-line atezolizumab (ATEZO, 1200 mg, q3w) in arm A versus early switch to ATEZO after run-in, followed by crossover to VEM + COB at PD1, in arm B. PFS from the start of run-in until PD1 was the primary endpoint (PFS1); secondary efficacy endpoints were OS, overall PFS (PFS2) and PFS3 (time from PD1 to PD after crossover, i.e. PD2) and best overall response rates (BORRs). - Results - The final analysis (median follow-up 57.0 months, interquartile range 22.7-63.0 months) confirmed longer PFS1 for continuous TT [arm A (69 patients) versus arm B (early switch, 66 patients); hazard ratio (HR) 0.61, 95% confidence interval (CI) 0.41-0.91, P = 0.006], but early switch to ICIs resulted in better long-term OS [4- and 5-year landmark OS 42% (95% CI 29% to 55%) and 40% (95% CI 27% to 53%) for arm A, and 53% (95% CI 38% to 65%) and 45% (95% CI 31% to 58%) for arm B; descriptive HR 1.17, 95% CI 0.71-1.91]. Absolute BORRs were 81% and 89%, respectively, with 15 (22%) and 19 (29%) patients achieving a complete response at least once along each sequence. At crossover, TT retreatment (arm B) resulted in higher PFS3 than second-line ICI (arm A). - Conclusions - Early switch to ICIs after TT run-in (arm B) led to an improved, although not statistically significant, 4- and 5-year landmark OS compared with arm A. No subgroups were identified for which a TT run-in provided clinical benefit. The number of patients developing brain metastasis and the time to brain metastasis were not improved by an early TT to ICI switch.
Online verfügbar: 8. Mai 2025, Artikelversion: 8. Mai 2025
V600 ist im Titel hochgestellt
Gesehen am 28.08.2025